ABIN1 Inhibits Inflammation through Necroptosis-Dependent Pathway in Ulcerative Colitis. (8th August 2022) - Bao, Jing; Ye, Bin; Ren, Yuhan
Abstract : Background . Ulcerative colitis (UC) is characterized by chronic, recurrent intestinal inflammation and intestinal epithelial injury including a wide range of epithelial cell death, ulcers, crypt abscesses, and the formation of fibrosis. The intestinal barrier dysfunction runs through the whole process of the occurrence and development of UC. A recent study revealed that an ubiquitin binding protein ABIN1 played a role in tissue homeostasis and autoimmunity diseases which involved in the anti-inflammatory response of intestinal epithelia cells. However, the roles of ABIN1 in ulcerative colitis pathogenesis remain unclear. Methods . The mRNA and protein expression level of ABIN1 and necroptosis-associated genes (RIPK1, RIPK3, and MLKL) were conducted to investigate the relationship between ABIN1 and necroptosis in clinical UC specimens. Subsequently, the dextran sodium sulfate (DSS)-induced mice colitis model was used to verify the ABIN1 function in vivo. Furthermore, we established ABIN1 gain and loss function assay in CACO-2 to confirm the mechanism in UC in vitro. Results . We found that ABIN1, RIPK1, RIPK3, and MLKL were upregulated in UC sample and DSS-induced colitis. Upon TNF- α stimulation in the intestinal epithelia cell line, overexpression of ABIN1 significantly inhibits necroptosis in the intestinal inflammation model along with the reduction expression of pro-inflammatory cytokines such as IL1B, IL6, IL8, and TNF- α . Blocking RIPK1 by Nec-1s in vivo and in vitro dramatically alleviated the colitis and cell death which shares the same phenotype with ABIN1 overexpression. Conclusion . Hence, the dysregulation of ABIN1 may relate to the uncontrolled necroptosis and inflammation in UC, and negatively regulate the occurrence and process of ulcerative colitis. ABIN1 activation may be considered a therapeutic strategy for UC.